The Middle East enters the twenty-first century - Freedman, Robert Owen (University Press of Florida, 2002)
''Succinctly laying out the problems and prospects for the Middle East in the new century, Freedman's book will be widely read in classrooms across the country.''--Glenn E. Robinson, Naval Postgraduate SchoolThis collection analyzes the impact of the three major developments of the latter part of the 20th century on the future of the Middle East in the 21st century: the Arab-Israeli peace process, the 1979 Islamic revolution in Iran, and the Iraqi invasion of Kuwait.